B2O3 reinforced polylactic acid/thermoplastic polyethylene glycol shape memory composites - Pekdemir, Mustafa Ersin; Kok, Mediha; Kanca, Muhammed Sait; Oner, Ecem Ozen; Pekdemir, Sibel; Inci, Sule; Tatar, Beyhan (Wiley, 2023)
Recently, there has been a great demand for boron-containing compounds (BCCs) with unique biological properties. The demand for the use of these compounds not alone but as additives in composite materials is increasing day by day. In this study, the effect of adding B2O3 compound to the blend of PLA and PEG polymers, which is an important biocompatible shape memory polymer, was investigated. In order to examine the effect of increasing B2O3 additive on the thermal properties of PLA-PEG blend, it was determined by using a Differential Scanning Calorimetry (DSC) and thermogravimetric analyzer (TGA), and it was seen that while the melting temperature of PEG decreased, the melting temperature of PLA increased. In addition, when the thermal stability of the composites was examined, increasing of thermal stability was observed with the addition of B2O3 and a three-step degradation occurred. It was determined that the B2O3/PLA-PEG composite was homogeneous by taking X-ray measurements and SEM measurements. The antimicrobial property of the PLA-PEG blend improved with the increasing B2O3 contribution were observed from the antimicrobial activity measurements of the composite against 4 different bacteria. However, it was determined that the PLA-PEG blend preserved its shape memory effect with increasing diboron trioxide contribution.
Keywords: antimicrobial acitivity; B2O3; blend; composite; poly lactic acid